Histopathological frequency of perianal neoplasms in dogs: casuistry of the Veterinary Pathology Laboratory of the National University of San Marcos (2005-2012) - Vicente R., Karla (2015)
The aim of this study was to determine the frequency of perianal neoplasms in dogs from samples histopathologically diagnosed in the Animal Pathology Laboratory of the National University of San Marcos in the period 2005 to 2012. A total of 52 cases of perianal tumors were diagnosed in 1283 cases of canine tumors (4.1%). The hepatoid gland adenoma was the most frequent (46.2%, 24/52).